2021
DOI: 10.1159/000514441
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Factors of the Retina and Their Role in Promoting Survival of Retinal Ganglion Cells: A Review

Abstract: Retinal ganglion cells (RGC) play a crucial role in the visual pathway. As their axons form the optic nerve, apoptosis of these cells causes neurodegenerative vision loss. RGC death could be triggered by increased intraocular pressure, advanced glycation end products, or mitochondrial dysfunction. In this review, we summarize the role of some neuroprotective factors in RGC injury: ciliary neurotrophic factor (CNTF), nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), vascular endothelial growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 120 publications
0
51
1
Order By: Relevance
“…This neurotrophin was downregulated in diabetic MC-specific VEGFR2 knockout mice, which may also play a synergistic role with VEGF or BDNF in supporting MC viability [ 9 , 36 ]. However, the underlying mechanisms of GDNF-mediated MC viability are most likely very different from that of BDNF [ 31 ]. The presence of these compensatory mechanisms provides an opportunity to find treatment strategies for neuronal degeneration in DR and other hypoxic retinal diseases in which VEGF is a therapeutic target for BRB breakdown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This neurotrophin was downregulated in diabetic MC-specific VEGFR2 knockout mice, which may also play a synergistic role with VEGF or BDNF in supporting MC viability [ 9 , 36 ]. However, the underlying mechanisms of GDNF-mediated MC viability are most likely very different from that of BDNF [ 31 ]. The presence of these compensatory mechanisms provides an opportunity to find treatment strategies for neuronal degeneration in DR and other hypoxic retinal diseases in which VEGF is a therapeutic target for BRB breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…MCs have been suggested as a major cellular source of retinal BDNF and other neurotrophins [ 29 , 30 ]. Although the role of neurotrophins in protecting ganglion cells under various stresses has been explored [ 31 , 32 , 33 ], little is known about the function of this family of trophic factors in diabetic and hypoxic retinas. It has been suggested that neurotrophins may play a role in keeping vascular integrity [ 4 ], which is in agreement with the suggestion that BDNF is a potential biomarker for DR [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, there was increased expression of ARAF, fibrinogen beta chain (FGB) and CLU. RAF kinases are major constituents of the mitogen-activated signaling pathway, regulating cell proliferation, differentiation, and cell survival [54,55]. However, the function of ARAF in the retina remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…PEDF is nontoxic [77]; 3. PEDF is multimodal and possesses neurotrophic [27], antiangiogenic [55], anti-inflammatory [78], antioxidant properties [79,80], all of which are beneficial for the treatment of several multifactorial retinal diseases; 4. PEDF is a soluble protein that can diffuse from the vitreous to the back of the eye and from the subconjuntiva to the retina [81][82][83][84]; 5.…”
Section: Discussionmentioning
confidence: 99%
“…Among the retinoprotective proteins of interest in ocular research, pigment epitheliumderived factor (PEDF) is relevant due to its well-established protective properties in the retina, in particular the photoreceptors [24,25], RPE cells [26] and in preventing neovascularization of the choroid and retina [27]. A variety of tissues express the gene Serpinf1 for PEDF, [25] which is altered in retinopathies and in tumor tissues as well [28].…”
Section: Biogenesismentioning
confidence: 99%